Prognostic significance of proline, glutamic acid, leucine rich protein 1 (PELP1) in triple-negative breast cancer: a retrospective study on 129 cases. Issue 1 (December 2015) - Zhang, Yanzhi; Dai, Jiali; McNamara, Keely; Bai, Bing; Shi, Mumu; Chan, Monica; Liu, Ming; Sasano, Hironobu; Wang, Xiuli; Li, Xiaolei; Liu, Lijuan; Ma, Ying; et al.
Abstract Background Triple-negative breast cancer (TNBC) is associated with an aggressive clinical course due to the lack of therapeutic targets. Therefore, identifying reliable prognostic biomarkers and novel therapeutic targets for patients with TNBC is required. Proline, glutamic acid, leucine rich protein 1 (PELP1) is a novel steroidal receptor co-regulator, functioning as an oncogene and its expression is maintained in estrogen receptor (ER) negative breast cancers. PELP1 has been proposed as a prognostic biomarker in hormone-related cancers, including luminal-type breast cancers, but its significance in TNBC has not been studied. Methods PELP1 immunoreactivity was evaluated using immunohistochemistry in 129 patients with TNBC. Results were correlated with clinicopathological variables including patient's age, tumor size, lymph node stage, tumor grade, clinical stage, histological type, Ki-67 LI, as well as clinical outcome of the patients, including disease-free survival (DFS) and overall survival (OS). Results PELP1 was localized predominantly in the nuclei of carcinoma cells in TNBC. With the exception of a positive correlation between PELP1 protein expression and lymph node stage (p  = 0.027), no significant associations between PELP1 protein expression and other clinicopathological variables, including DFS and OS, were found. However, when PELP1 and Ki-67 LI were grouped together, we found that patients in the PELP1/Ki-67 double high group (n = 48) demonstrated significantly reduced DFS (p  = 0.005, log rank test) and OS (p  = 0.002, log rank test) than others (n = 81). Multivariable analysis supported PELP1/Ki-67 double high expression as an independent prognostic factor in patients with TNBC, with an adjusted hazard ratio of 2.020 for recurrence (95 % CL, 1.022–3.990;p  = 0.043) and of 2.380 for death (95 % CL, 1.138–4.978;p  = 0.021). Conclusions We found that evaluating both PELP1 and Ki-67 expression in TNBC could enhance the prognostic sensitivity of the two biomarkers. Therefore, we propose that PELP1/Ki-67 double high expression in tumors is an independent prognostic factor for predicting a poor outcome for patients with TNBC.